Estrategias competitivas para la exportación de banano orgánico de la Asoguabo hacia California, Estados Unidos. - Zambrano Valarezo, Juan Sebastian; Urgiles Carabajo, Martha Ines (Universidad Técnica de Machala, 2022)
Banana exports have experienced a favorable outlook for the production of Ecuadorian organic bananas, however the war between Russia and Ukraine had repercussions in the first months of this year for the sector that registered economic damage, causing exporters such as ASOGUABO to join forces for redirections its commercialization process towards the North American market: the United States and Canada, which has generated that it joins the competition race with other exporters and countries that have found their commercial objective in that niche. It is for this reason that there is certainly an advantage in that ASOGUABO is already working in the North American market, which requires competitive strategies to differentiate itself from the current competition. For this reason, the present work raised as its main objective to determine the competitive strategies that allow the export of organic bananas to California, the United States, the same that arises after asking ourselves: What is the competitive strategy that ASOGUABO is using to be able to reach other markets? ? In such a way that it was through the application of the inductive and deductive method in addition to the synthetic analysis on the subject where it was necessary to resort to the survey and interview directed towards the producer partners of the institution and administrative personnel that were a key piece to determine the competitive strategies currently used by ASOGUABO. In conclusion, the main competitive strategies used by the association is the cost strategy, which should be strengthened and implemented together with the focus strategy for the commercialization of organic bananas towards California, a market that could be verified to have a majority population compared to California other states, with a tendency to consume healthy products.
La exportaciones bananeras han experimentado un favorable panorama para la producción de banano orgánico ecuatoriano, sin embargo el conflicto bélico entre Rusia y Ucrania repercutió en los primeros meses del presente año para el sector que registró afectaciones económicas, haciendo que exportadoras como la ASOGUABO reúnan esfuerzos para redireccionar su proceso de comercialización hacia el mercado Norteamericano: Estados Unidos y Canadá, lo que ha generado que se una a la carrera de competencia con otras exportadoras y países que han encontrado en ese nicho su objetivo comercial. Es por esta razón, que ciertamente existe una ventaja en que la ASOGUABO ya se encuentra trabajando en el mercado norteamericano por lo que se requiere estrategias competitivas para diferenciarse de la competencia actual. Por ello el presente trabajo planteó como su principal objetivo determinar las estrategias competitivas que permita la exportación de banano orgánico hacia California, Estados Unidos la misma que surge luego de plantearnos ¿Cuál es la estrategia competitiva que está utilizando la ASOGUABO para poder llegar a otros mercado? De tal manera que fue a través de la aplicación del método inductivo y deductivo además del análisis sintético sobre la temática en donde fue necesario recurrir a la encuesta y entrevista dirigida hacia los productores socios de la institución y personal administrativo que fueron pieza clave para determinar las estrategias competitivas que actualmente utiliza la ASOGUABO. En conclusión, las principales estrategias competitivas que utiliza la asociación es la estrategia de costes, la cual deberá afianzarse e implementarse junto a la estrategia de enfoque para comercialización del banano orgánico hacia California, mercado que se pudo comprobar cuenta con una población mayoritaria en comparación a otros estados, con tendencia a consumir productos saludables.
Keywords: BANANO; ESTRATEGIAS; EXPORTACION; MERCADO